Oligo-Asp Tag/Zn(Il) Complex Probe as a New Pair for Labeling and Fluorescence Imaging of Proteins. - Ojida, Akio; Honda, Kei; Shinmi, Daisuke; Kiyonaka, Shigeki; Mori, Yasuo; Hamachi, Itaru (Journal of the American Chemical Society, 2006)
To accomplish the selective labeling of a specific protein in complicated biological systems, a peptide tag incorporated into the protein and a complementary small molecular probe are required. Although a variety of peptide tag/probe pairs have been developed as molecular tools for protein analyses, the availability of pairs suitable for real-time imaging of proteins is still limited. We now report a new peptide tag/artificial probe pair composed of a genetically encodable oligo-aspartate sequence (D4 tag, (D4), n = 1-3) and the corresponding multinuclear Zn(ll) complexes (Zn(ll)-DpaTyrs). The strong binding affinity of the Zn(ll)-DpaTyr probes with the D4 tag was a result of the multiple coordination bonds and the multivalent effect. It was measured quantitatively by isothermal titration calorimetry. The high affinity between the tag and the probe, indispensable for the selective protein labeling, enabled the pair to be used for the labeling and fluorescence imaging of a membrane-bound receptor protein tethering a triply repeated D4 tag ((D4)) in an intact cell configuration without significantly affecting the receptor signal transduction.